Reviews - Bauer, Henry H.; Alvarado, Carlos S.; Williams, Bryan J.; Cranganu, Constantin; Jenkins, Hannah; Davidson, Michael; Rodeghier, Mark; Shuker, Karl P. N.; Nahm, Michael; Zangari, Wellington; et al. (Journal of Scientific Exploration, 2011)
Essay Review: Medicine To Make You Mad Anatomy of an Epidemic: Magic Bullets, Psychiatric Drugs, and the Astonishing Rise of Mental Illness in America by Robert Whitaker Henry H. Bauer Essay Review: Apparitions of the Living: The Views of William H. Harrison and Gabriel Delanne Spirits Before Our Eyes by William H. Harrison Les Apparitions Matérialisées des Vivants & des Morts. Vol. 1: Les Fantômes de Vivants [Materialized Apparitions of the Living and of the Dead. Vol. 1: Phantoms of the Living] by Gabriel Delanne Carlos S. Alvarado Phantasms of the Living by Edmund Gurney, Frederic W. H. Myers, and Frank Podmore Bryan J. Williams Nonsense on Stilts: How To Tell Science from Bunk by Massimo Pigliucci Constantin Cranganu Nonsense on Stilts: How To Tell Science from Bunk by Massimo Pigliucci Hannah Jenkins The Logical Leap: Induction in Physics by David Harriman Michael Davidson Paranormal America: Ghost Encounters, UFO Sightings, Bigfoot Hunts, and Other Curiosities in Religion and Culture by Christopher D. Bader, F. Carson Mencken, and Joseph O. Baker Mark Rodeghier Loch Ness, Nessie, & Me: The Truth Revealed by Tony Harmsworth Karl P. N. Shuker Conscious Connections: About Parapsychology and Holistic Biology by Göran Brusewitz Michael Nahm Science & Spirit by Hernani Guimarães Andrade Wellington Zangari & Fatima Regina Machado The Sixth Sense Reader edited by David Howes Patric Giesler